Eosinophilic pleural effusion due to Spirometra mansoni spargana: a case report and review of the literature. (May 2015) - Lin, Quan; Ouyang, Jin-Sheng; Li, Jian-Min; Yang, Li; Li, Yu-Ping; Chen, Cheng-Shui
Summary: A 36-year-old female presented with an eosinophilic pleural effusion. The eosinophilic pleural effusion was considered to have been caused by a parasitic infection. Spirometra mansoni spargana was confirmed by semi-rigid thoracoscopy. About 2 months after treatment with praziquantel for 3 days, the pleural effusion had disappeared on the chest roentgenogram.